Residual Chlorine Induced Cationic Active Species on a Porous Copper Electrocatalyst for Highly Stable Electrochemical CO2 Reduction to C2+. (8th April 2021) - Li, Minhan; Ma, Yuanyuan; Chen, Jun; Lawrence, Robert; Luo, Wei; Sacchi, Marco; Jiang, Wan; Yang, Jianping
Abstract: Electrochemical carbon dioxide (CO2 ) reduction reaction (CO2 RR) is an attractive approach to deal with the emission of CO2 and to produce valuable fuels and chemicals in a carbon‐neutral way. Many efforts have been devoted to boost the activity and selectivity of high‐value multicarbon products (C2+ ) on Cu‐based electrocatalysts. However, Cu‐based CO2 RR electrocatalysts suffer from poor catalytic stability mainly due to the structural degradation and loss of active species under CO2 RR condition. To date, most reported Cu‐based electrocatalysts present stabilities over dozens of hours, which limits the advance of Cu‐based electrocatalysts for CO2 RR. Herein, a porous chlorine‐doped Cu electrocatalyst exhibits high C2+ Faradaic efficiency (FE) of 53.8 % at −1.00 V versus reversible hydrogen electrode (VRHE ). Importantly, the catalyst exhibited an outstanding catalytic stability in long‐term electrocatalysis over 240 h. Experimental results show that the chlorine‐induced stable cationic Cu 0 /Cu + species and the well‐preserved structure with abundant active sites are critical to the high FE of C2+ in the long‐term run of electrochemical CO2 reduction. Abstract : A porous Cu electrocatalyst showed long‐term stability for over 240 h in the CO2 reduction reaction (CO2 RR). The mixed Cu 0 and Cu + oxidation state induced by the residual Cl and the porous sheet‐like morphology were the key to the catalytic stability.